IMPROVING SANTRI'S ENTREPRENEURSHIP MOTIVATION THROUGH PROBLEM-BASED LEARNING APPROACH ENTREPRENEURSHIP TRAINING - Fitriana, Dina; Nurhayati, Sri (IKIP Siliwangi Bandung, 2024)
The purpose of this study is to determine how to improve santri's motivation for entrepreneurship and to examine the impact of entrepreneurship motivation training in salafiah santri using a Problem Based Learning approach. The technique and methods utilized in this study are qualitative with descriptive methods. The research was done in salafiah pesantren in Cimahi City, and the subjects were six santri individuals who had previously attended training or had never attended. Data collecting techniques include observing, interviewing, and documenting. According to the data analysis, there has been a considerable growth in entrepreneurial motivation and interest in starting a business. From the research findings it can be concluded that conducting entrepreneurship training for students will significantly assist them in starting a successful business and increasing their confidence as entrepreneurs.